(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the semantic units that create the image in the stories of Utkir Hoshimov. It is evidenced that the author was able to create a character using linguistic units, to use various language tools to create a memorable and vivid character image, to deepen the psyche of characters, to use various details, images of natural phenomena, external factors addressed in order to fill his character.